Isolation of antiplasmodial naphthylisoquinoline alkaloids from Ancistrocladus sp. through bioassay-guided fractionation - Maharaj, Vinesh J. (University of Pretoria, 2020)
Dissertation (MSc)--University of Pretoria, 2019.